Utilização da cinza do bagaço de cana-de-açúcar na síntese de zeólita A. para purificação de etanol com teste em coluna piloto de adsorção - Figueirêdo, Nyara Aschoff Cavalcanti (2020)
The generation of energy occurs with the use of sugarcane bagasse as fuel in boilers, obtaining sugarcane bagasse ash as final residue, the only destination practiced is the use in washing machines and the sending of surplus water. In addition, ethanol dehydration in these industries, to production of anhydrous alcohol, uses toxic solvents in the distillation process. In order to mitigate the environmental impacts generated by these solvents and the inadequate deposition of residues such as cane berry ash, the recording of zeolites A was carried out, using the sugarcane bagasse ash as a precursor to silicates for their formation. Also carried out, with ethanol purification efficiency tests, the designs of an adsorption column on a on a bank scale and one on pilot production scale, using commercial zeolites and produced in this work. A composition of sugarcane bagasse ash and synthesized materials were investigated by X-ray fluorescence analysis (FRX). The synthesized materials were also characterized by X-ray diffraction analysis (XRD) to demonstrate the formation of type A zeolites and their crystallinity. After characterization, the most promising material for use in dehydration, an SCBANa, underwent tests on the adsorption column on the bank scale, just as the commercial zeolite (ZC3A) was tested on the bank scale and on an experimental scale. Ethanol underwent density analysis and chromatography, before and after the process to demonstrate the efficiency of dehydration and removal of contaminants by SCBANa. The results demonstrated as bagasse ash have a high content of silicates in its composition, being a potential source for the manufacture of adsorbents and catalyst supports. The characterization of the synthesized materials shows the formation of zeolite A, the same that shows some details that show the presence of other residual components of the engraving process, with good crystallinity and intensity, highlighting the material called SCBANa, which predominantly contains the use of presence of zeolites type 4A and 5A, both are promising for the ethanol purification process